A Note on Danish Living Standards through Historical Wage Series, 1731-1913 - Ekaterina Khaustova; Paul Sharp (European Historical Economics Society (EHES), 2015)
This paper makes use of published information on wages and prices in Denmark to construct consistent real wage series for the years 1731 to 1913, which can be compared to other countries. Placing Denmark in a comparative perspective demonstrates that from being a relatively poor, backward economy in the eighteenth century, by the 1870s Copenhagen had one of the highest standards of living in Europe. Interestingly, this was before the introduction of stream-driven cooperative creameries, which leads us to speculate that high wages might have been an incentive to mechanize, as well as being a consequence of the later productivity increases in agriculture in particular.
Keywords: N33; 330; Copenhagen; Denmark; prices; real wages